Characterization of Interfacial Charge‐Transfer Photoexcitation of Polychromium‐Oxo‐Electrodeposited TiO2 as an Earth‐Abundant Photoanode for Water Oxidation Driven by Visible Light. Issue 10 (6th October 2016) - Chandra, Debraj; Tsuriya, Ryougen; Sato, Tsubasa; Takama, Daisuke; Abe, Naoto; Kajita, Masashi; Li, Dong; Togashi, Takanari; Kurihara, Masato; Saito, Kenji; Yui, Tatsuto; Yagi, Masayuki
Abstract: Polychromium‐oxo‐deposited TiO2 (Cr III x O y /TiO2 ) electrodes were fabricated by a simple electrochemical technique by using different TiO2 basal electrodes (anatase, rutile, and mixed polymorphic phases P25) as earth‐abundant photoanodes for visible‐light‐driven water oxidation. The high‐resolution transmission electron microscopy (HR‐TEM) observation illustrated that an Cr III x O y layer with approximately 2–3 nm thickness was formed on the surface of the crystalline TiO2 particles. Upon visible‐light irradiation of the electrodes, the photoanodic current based on water oxidation was generated at the Cr III x O y /TiO2 electrodes. However, the wavelength (below 620 nm) for photocurrent generation at Cr III x O y /TiO2 ‐rutile was longer than that (below 560 nm) at Cr III x O y /TiO2 ‐P25 by 60 nm, which is in agreement with the difference (0.2 eV) in the conduction band (CB) edge energy between rutile and anatase TiO2 . This gives a quantitative account for the photocurrent generation based on interfacial charge transfer (IFCT) from Cr 3d of the deposited Cr III x O y layer to the TiO2 CB. The photocurrent generated for Cr III x O y /TiO2 ‐rutile was higher than that for Cr III x O y /TiO2 ‐anatase, which is ascribed to 1) more effective Cr III x O y deposition on the rutile particles, 2) a larger electrolyte/Cr III x O y interface for water oxidation as a result of smaller rutile particles (ca. 30–40 nm) compared with larger P25 particles (ca. 40–80 nm), and 3) more effective use of visible light owing to the low energy IFCT transition of rutile. Abstract : Earth‐abundant photoanode for water splitting : Polychromium‐oxo‐deposited TiO2 (Cr III x O y /TiO2 ) electrodes were fabricated by a simple electrochemical technique by using different TiO2 basal electrodes (anatase, rutile, and mixed polymorphic phases P25) as earth‐abundant photoanodes. Visible‐light‐driven water oxidation was achieved based on interfacial charge transfer (IFCT) from Cr 3d of the Cr III x O y layer to the TiO2 conduction band.